Personalized Psychotherapy Informed by Person in Context Assessment: A Single Subject Study - Paup, Sierra R.; Scott, Walter D.; Lin, Belinda (Journal of personality assessment, 2025)
We examined the therapeutic utility of personalized psychotherapy informed by social cognitive personality assessment. Specifically, Person in Context Assessment (PICA) assesses both the social cognitive personality structures (i.e., temperament, self-schemata, goals, and moral standards) and the personality processes (i.e., situation-based patterns of appraisals, affects, behaviors) characterizing an individual. Both the client and the therapist received PICA feedback and specific therapeutic recommendations targeting social cognitive personality structures and processes that appeared to contribute most to the client's distress and dysfunction. After the therapist began implementing these PICA-informed interventions, the client reported significant decreases in depressive symptoms that remained stable over two months, culminating in a successful termination of therapy. Evidence suggested that decreases in depression coincided with the client showing improvements in the personality structures and processes that were targeted by the PICA-informed therapeutic interventions. The client's perceptions of therapy credibility and expectancy, as well as their motivation to change, also appeared to improve. However, there was no evidence that the PICA feedback improved the client's self-understanding or self-efficacy. Our findings provide initial support for PICA's therapeutic utility.